Representasi Budaya Keluarga Islam dalam Novel Tekad Karya Wahyudi Pratama sebagai Alternatif Bahan Ajar Sastra di SMA/MA - Dwi Rahmi Supradini; Bagus Wahyu Setyawan (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2025)
Literary works are works of art written using beautiful language and words to convey the author's thoughts and ideas to the audience. The stories in the novel raise many life values ​​such as religious values ​​and moral values. One novel that contains religious values ​​and presents an inspiring story that is appropriate to the lives of today's teenagers is the novel Tekad by Wahyudi Pratama. The aims of this research are (1) to describe Islamic family culture in the novel Tekad, and (2) the relevance of the novel Tekad as an alternative literary teaching material in SMA/MA. This research is a type of text study using a literary sociology approach. Text study is one of the methods within the scope of qualitative research. Researchers use a literary sociology approach in analyzing Islamic family culture in this novel. Literary sociology is a literary study that views works as representations of society. There are two sources of data in this research, namely the novel Tekad by Wahyudi Pratama and Indonesian language teachers. The values ​​in the novel teach good behavior and etiquette such as courtesy, mutual respect and mutual cooperation. This novel can be used as an alternative teaching material for learning to listen to literature for class